Breast cancer trends in women younger than 40 years in Brazil. (June 2022) - Bonadio, Renata Colombo; Moreira, Otavio Augusto; Testa, Laura
Abstract: Background: A recent Brazilian populational database analysis showed a concerning increase in breast cancer mortality rates among patients under 40 years. We aimed to evaluate the trends in the proportion of new breast cancer cases and deaths occurring in patients younger than 40 years over the last decade in Brazil. Methods: We evaluated all consecutive breast cancer patients treated from 2009 to 2020 in a Brazilian tertiary cancer center. The proportions of new cases and deaths in patients younger than 40 years was compared between two time periods (2015–2020 versus 2009–2014) using Chi-squared test. Linear regression was used to evaluate the trends in the proportion of new cases and deaths in young patients over the years. Results: From 2009 to 2020, a total of 12, 569 breast cancer patients started treatment at our institution; 1441 were younger than 40 years. From 2009 to 2014, 9.9% (95% CI 9.2–10.7%) were patients younger than 40 years compared to 12.9% (95% CI 12.1–13.8%) from 2015 to 2020. Similarly, the proportion of deaths among breast cancer patients younger than 40 years increased during the period (2009–2014: 9.6%, 95% CI 7.8–11.6%; 2015–2020: 12.4%, 95% CI 10.9–14%). The linear regression model showed a trend for an increasing proportion of new breast cancer cases occurring in patients under 40 years (P = 0.005). Proportion increased from 7.9% (95% CI 6.2–9.8%) in 2009 to 21.8% (95% CI 19.1–24.8%) in 2020. The trend for the increase in the proportion of deaths in this young population was also observed in the linear regression model (P = 0.01). Conclusions: The proportion of new breast cancer cases and deaths among patients younger than 40 years has increased in a public Brazilian cancer center over the past decade. These results raise the concern for the need to reconsider primary and secondary prevention strategies for young women. Highlights: Breast cancer cases and deaths among women under 40 years is increasing in Brazil. In 2021, 21.8% of breast cancer cases in a tertiary cancer center were in young ages. Health policies are required to improve prevention strategies for this young group.